Upaya Re-Definisi Korporasi dalam Undang-Undang Nomor 1 Tahun 2023 - Prasetya, Muhammad Djaelani; Ratnawati, Ratnawati (UNES Law Review, 2023)
The phenomenon of community associations or associations that do not have legal entities leads this research to seek a re-definition of corporations in Law Number 1 Year 2023. The research is conducted normatively with a historical, statutory and case approach. This will be analyzed qualitatively in order to answer legal questions. The research found that First, the history of corporations in the United States has described the development of terms, understanding, bad behavior, criminal administration, prosecution, criminal liability to deferred prosecution aggrement. Second, the efforts to redefine corporation are divided into 3 (three) things, namely 1) based on legislation, where 7 (seven) phases of development of the meaning of corporation are found, both indirectly and directly; 2) based on the existence of the Business Competition Supervisory Commission which has a connection with corporate crime and can cause problems in the future if it is connected to Article 146 of the New Criminal Code; and 3) based on a systematic review of the New Criminal Code which can cause problems such as the existence of terms without understanding or explanation, the existence of almost the same meaning without explanation, the contradiction of terms and the use of unnecessary words.